Liberalism and prostitution - De Marneffe, Peter, 1957- (New York ; Oxford : Oxford University Press, 2010)
In this volume Peter de Marneffe argues that although most prostitution is voluntary, paternalistic prostitution laws in some form are nonetheless morally justifiable.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Prostitution; Liberalism; Paternalism; Civil rights